Differences between the Assessment of the Behavior of a Child Raised in a Care and Educational Institution (Foster Care) and a Child Raised in a Family - Gamian-Wilk, Małgorzata; Madeja-Bień, Kamila; Domagała-Jędrzejewska, Sylwia (INSTED: Interdisciplinary Studies in Education & Society, 2018)
Nowadays, when family ties are more and more relaxed, and the relationships between family members are not strong, the value of the context of the family's origin should not be significant in its assessment. However, many times we hear about unequal and even stigmatizing treatment of people due to this factor. This is not just the case of adults, but also of children. The way of perceiving another human being through such prism can cause long-lasting consequences, resulting even in social exclusion. The text reports the results of research conducted among 130 people (including 30 teachers), whose aim was to check the perception of pupils from care and educational institutions. It was shown that it was only the teachers who stigmatized a child's behaviour, if it was a charge of the foster care institution, compared to the same behaviour of the child raised in a family.